Source Based Waste Management in Padangtegal Village, Ubud District, Gianyar Regency - I Nyoman Gede Sugiartha; A. A. Sagung Laksmi Dewi; Luh Putu Suryani; Ni Made Puspasutari Ujianti; I Made Gandra; Ayu Prasetya Dewi; Ni Putu Laksmi Krisnina Maharai (Fakultas Hukum, Universitas Warmadewa, 2023)
Garbage is a problem faced in almost all parts of the world. Seeing the many waste problems that occur, the Padangtegal Traditional Village built a compost house as a form of village concern for waste problems. The implementation of waste management in the Padangtegal Traditional Village has been going well according to applicable regulations, awig-awig and Pararem are used as a legal basis or guideline for implementing the implementation of waste management by the Padangtegal Traditional Village Compos House, regulated through the Padangtegal Traditional Village Pararem Number: 04/DPP/ VI/2015 concerning the Beauty of Palemahan Village but in the awig-awig it has not been specifically regulated. There needs to be public awareness to improve the standard of clean and healthy living. The solution offered to partners is to compile new regulations that are more detailed in terms of managing the implementation of source-based waste management as well as conducting FGDs and socializing the importance of good waste management. The aims of this research is to develop new pararem that are more detailed in terms of managing the implementation of source-based waste management as well as conducting FGDs and socializing the importance of good waste management.